Glia and zinc in ageing and Alzheimer’s disease: a mechanism for cognitive decline? - Hancock, Sara M. (Frontiers Media S.A., 2014)
Normal ageing is characterized by cognitive decline across a range of neurological functions, which are further impaired in Alzheimer’s disease (AD). Recently, alterations in zinc (Zn) concentrations, particularly at the synapse, have emerged as a potential mechanism underlying the cognitive changes that occur in both ageing and AD. Zn is now accepted as a potent neuromodulator, affecting a variety of signaling pathways at the synapse that are critical to normal cognition. While the focus has principally been on the neuron: Zn interaction, there is a growing literature suggesting that glia may also play a modulatory role in maintaining both Zn ion homeostasis and the normal function of the synapse. Indeed, zinc transporters (ZnT’s) have been demonstrated in glial cells where Zn has also been shown to have a role in signaling. Furthermore, there is increasing evidence that the pathogenesis of AD critically involves glial cells (such as astrocytes), which have been reported to contribute to amyloid-beta (Aβ) neurotoxicity. This review discusses the current evidence supporting a complex interplay of glia, Zn dyshomeostasis and synaptic function in ageing and AD.